(untitled) (Journal of Fatima Jinnah Medical University, 2018)
Objective: To determine the rate of caesarean sections (CS) and frequency of their various indications. Study Design: Cross-sectional study. Setting: Department of Obstetrics and Gynaecology, Units 1 and 2, Arif Memorial Teaching Hospital (AMTH), Lahore. Duration: One year, from 1st January 2014 to 31st December 2014. Methods: All deliveries at gestational age 28 weeks and greater in the hospital during 2014 were included. Data were taken from labour room and theatre registers. Patients’ hospital number, booking status, parity, date of delivery, type of delivery and indications of emergency and elective caesarean sections were recorded. Results: All deliveries at gestational age 28 weeks and greater in the hospital during 2014 were included. Out of 1100, Multigravidae were 55.1% (606), whereas primigravidae were 44.9% (494). 62.4% (686) were caesareans (CS) and 37.6% (414) were vaginal deliveries. 94.92% (393) were spontaneous vaginal deliveries, 2.41% (10) vaginal births after caesarean (VBACs), 1.93% (8) were assisted breech deliveries (ABDs), 0.48% (2) vacuum deliveries and 0.24% (1) outlet forceps delivery. Out of 686 CS, 62.24% (427) were emergency CS (Em CS) and 37.76% (259) were elective CS (El CS). Conclusion: Currently AMTH has a high CS rate of 62.4%. If quality of vaginal deliveries is improved and CS in primigravidae is avoided as far as possible ,the number of ElCS can be eventually decreased. Health policy makers and managers should collaborate in designing strategies to improve expertise of dais and general practitioners and improve awareness in population to curtail the number of high risk cases with multiple indications referred for EmCS.